2002
DOI: 10.1099/0022-1317-83-7-1613
|View full text |Cite
|
Sign up to set email alerts
|

Mixed patterns of transmission of human herpesvirus-8 (Kaposi’s sarcoma-associated herpesvirus) in Malawian families

Abstract: To study transmission patterns of human herpesvirus-8 (HHV-8) (Kaposi's sarcoma-associated herpesvirus) in families in Malawi, nucleotide sequences derived from two hypervariable loci of the HHV-8 genome, the V1 and V2 regions of open reading frame K1 (K1/V1 and K1/V2, respectively), were amplified from blood and mouth rinse samples of 22 patients with treated and untreated Kaposi's sarcoma (KS) and their first-degree relatives (n l 67). In patients with KS, vincristine therapy was significantly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…However, recent epidemiology studies suggested that oral transmission of KSHV does occur among healthy populations (14,15). Complicating the transmission issue, the identities of the cell types harboring KSHV in vivo in the oral cavity and producing the virus detected in saliva are not known.…”
mentioning
confidence: 99%
“…However, recent epidemiology studies suggested that oral transmission of KSHV does occur among healthy populations (14,15). Complicating the transmission issue, the identities of the cell types harboring KSHV in vivo in the oral cavity and producing the virus detected in saliva are not known.…”
mentioning
confidence: 99%
“…Like HIV Env, the extracellular domain of the K1 protein is also extremely variable. Particularly, two 40-amino-acid blocks at the extracellular domain of K1, variable regions 1 and 2 (V1 and V2, respectively), show as much as 85% divergence at the nucleotide level and 60% divergence at the amino acid level (7,16,23,47). Different V1 and V2 regions seem to correspond to different geographic areas (7,16,23,47).…”
mentioning
confidence: 99%
“…Particularly, two 40-amino-acid blocks at the extracellular domain of K1, variable regions 1 and 2 (V1 and V2, respectively), show as much as 85% divergence at the nucleotide level and 60% divergence at the amino acid level (7,16,23,47). Different V1 and V2 regions seem to correspond to different geographic areas (7,16,23,47). Studies of K1 alleles from various KSHVinfected tissues have defined four major subtypes of K1 (A, B, C, and D) and 13 distinct variants and clades similar to those found for the HIV Env protein (16,19,47).…”
mentioning
confidence: 99%
“…Besides its regional homology with the Ig family, the extracellular domain of K1 also contains conserved regions (C1 and C2) and variable regions (V1 and V2). Particularly, two 40-amino-acid blocks at the extracellular V1 and V2 domains of K1 show as much as 85% divergence at the nucleotide level and 60% divergence at the amino acid level (7,20,27,53). In addition, the amino-terminal region of K1 specifically interacts with the chains of B-cell antigen receptor (BCR) complexes, and this interaction inhibits the intracellular transport of BCR, resulting in downregulation of BCR surface expression (31).…”
mentioning
confidence: 99%